DEBATE, SELF-EFFICACY, AND DECISION MAKING IN EAST JAVA ENGLISH COMPETITION - Piranti Astri Pertiwi; Ary Setya Budhi Ningrum; Fathor Rasyid (Universitas Islam Nahdlatul Ulama Jepara, 2022)
In the era of globalization, self-efficacy and decision-making are needed to complete self-quality. Many education experts believe that debate is closely correlated with self-efficacy and decision-making. Therefore, this study investigates the correlation between debate, self-efficacy and decision-making. This correlation study involved 67 students in the English Debate competition at the East-Java English Club (EJEC) 4 2020. 25 questionnaire items with Yes/No options were used to determine student debate perceptions and two Likert scale questionnaires, each consisting of 26 items for measuring decision making and 30 items to measure self-efficacy were also given to students. The Kendall's Tau Correlation ver.21 for windows demonstrates a moderate correlation between debate and decision-making (r=.436), debate with self-efficacy (r=.513), and self-efficacy and decision-making (r =,827). From these results, it can be concluded that there is a significant correlation between debate and decision making, debate with self-efficacy, and self-efficacy with decision-making. It also bringsrecommendations for further researchers to find out more about students' perspectives and debate coaches regarding the debate method to develop students' decision-making abilities and self-efficacy